Public health impact and harm reduction implications of xylazine-involved overdoses: a narrative review - David T. Zhu (BMC, 2023)
Abstract Introduction Xylazine, an α2-adrenoceptor agonist sedative commonly used in veterinary medicine, is not approved for human use. Nevertheless, xylazine-involved overdose rates have surged in recent years, fueled by an increasingly toxic and synthetic illicit drug supply in North America. Methods This narrative review assessed major epidemiological trends in xylazine-involved overdoses in North America, aiming to identify harm reduction priorities. A literature search was conducted using four bibliographic databases (PubMed, Scopus, Embase, and ScienceDirect) and three preprint servers (medRxiv, bioRxiv, and Europe PMC) on May 28, 2023, to capture articles related to combinations of keywords such as "xylazine", "opioid", and "harm reduction". Results Xylazine emerged as an adulterant in Puerto Rico in 2001, likely diverted from veterinary supplies. By the mid-2010s, it began proliferating across unregulated US drug markets, often contemporaneously with illicitly manufactured fentanyl (IMF), displaying characteristics of a syndemic. Initially concentrated in Northeastern regions (e.g., Philadelphia, Connecticut, Maryland), xylazine-involved overdoses later extended to the Rust Belt, Southern, and Western regions of the USA in the late 2010s and early 2020s. During this time, xylazine-involved overdoses also surged in Canada, particularly in Western provinces (British Columbia and Alberta) and Ontario with established IMF-dominated unregulated drug markets. Discussion Over the past two decades, xylazine-involved overdoses have been rapidly rising in North America and exhibit few signs of slowing down, representing a serious public health epidemic. Numerous factors may have contributed to this, including limited epidemiological surveillance and drug checking for xylazine and emerging novel adulterants; further, barriers to comprehensive, trauma-informed, non-stigmatizing treatment and social services have also exacerbated this issue. While several epidemiological and ethnographic studies have assessed these factors in the USA, limited evidence is available in Canada where xylazine emerged more recently. This underscores the need for additional research and harm reduction measures. Conclusion Harm reduction-informed public health guidelines and programs are urgently needed to promote a safer supply, strengthen the healthcare system capacity to prevent and respond to xylazine-involved overdoses, and address social and structural disparities in health outcomes.